2020
DOI: 10.1111/joor.12925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time in function on the predictability of short dental implants (≤6 mm): A meta‐analysis

Abstract: Purpose To analyse randomised controlled clinical trials (RCTs) and prospective cohort studies reporting on the survival and failure rates of functionally loaded short implants (SI) based on the actual length of time in function. Materials and methods This meta‐analysis was conducted according to PRISMA guidelines for systematic reviews. Electronic and manual searches were conducted to identify RCTs and prospective cohort studies reporting survival and complication rates of short dental implants (≤6 mm) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
0
23
0
5
Order By: Relevance
“…These authors stress the importance of "undersizing" the implant site in order to obtain correct primary stability. Placement of short implants in these situations have similar survival results resulting in 96% survival rates [35].…”
Section: Discussionmentioning
confidence: 96%
“…These authors stress the importance of "undersizing" the implant site in order to obtain correct primary stability. Placement of short implants in these situations have similar survival results resulting in 96% survival rates [35].…”
Section: Discussionmentioning
confidence: 96%
“…In 2020, Rameh et al, limiting the inclusion criteria to a minimum of five-year follow-up, reported for 5/6 mm-long implants, an average of 95.54%, ranging between 86.7 and 98.5%, survival rate in the maxilla, and a 94.39%, ranging between 86.7 and 100%, in mandible [ 7 ]. Vazouras et al, including the studies on ≥4 and ≤6 mm ultra-short implants with a minimum follow-up of three years, calculated a 4% overall failure increasing to 10% after that [ 9 ]. The first reports on 4 mm ultra-short implants in posterior mandibles found a survival rate of 95.7% and 92.3%, after one and two years, respectively [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the studies convey that short implants could be a better choice considering the morbidity, the costs, and the duration of the reconstructive approaches. Nevertheless, a time-dependent higher risk of failure of ≤6 mm-long implants emerged, with a wide range of the survival rates, from 86.7% to 100%, and a calculated 24% higher risk for 1–5 years follow-up than with longer implants [ 9 ]. Regarding ≥5 years of loading of ≤5 mm-long screws, the literature is so far insufficient to recommend this approach [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of our study presented high survival rates at the two-year follow-up for the different types and lengths of the evaluated implants, caution should be taken when assessing the obtained results since failure rates could depend on time in function. A recently published meta-analysis [53] evaluated the short implants' (≤6 mm) failure rates based on time in function, and the results demonstrated a time-dependent decrease in the survival rate of single short implants in the posterior area. Furthermore, some long-term studies reported that, between the third and fifth years in function, the risk of short implant failure increases significantly [33,44].…”
Section: Discussionmentioning
confidence: 99%